PENGEMBANGAN BAHAN AJAR PENDIDIKAN NILAI DAN MORAL BERBASIS CASE METHOD UNTUK MENGEMBANGKAN CIVIC INTELLIGENCE MAHASISWA PGSD UNIVERSITAS BENGKULU - Susanti, Atika; Febri Ariffiando, Nady (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Value and moral education is an integral part of character development and social readiness, particularly for students in the Elementary School Teacher Education Program (PGSD). However, teaching materials with the right learning approach to foster a deep understanding of these values and develop civic intelligence remain an unmet need. This study aims to develop value and moral education teaching materials based on the Case Method to enhance the civic intelligence of PGSD students at Universitas Bengkulu. The development method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data analysis was conducted through qualitative and quantitative analysis. This research successfully developed value and moral education teaching materials based on the Case Method to support the development of civic intelligence in PGSD students at Universitas Bengkulu. Based on the validation results, the teaching materials achieved an average Aiken’s V score of 90%, indicating that the materials are highly valid, engaging, and practical, thus suitable for use. The implementation of the teaching materials in learning showed active student engagement, an improved understanding of values and morals, and better ability to relate case studies to civic intelligence. Civic intelligence measurements also demonstrated improvements across all indicators, with an average gain score of 0.682, which falls under the moderate category. This reflects the effectiveness of the teaching materials in enhancing students' civic intelligence.